2013
DOI: 10.1111/jace.12486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postdensification Annealing upon Microstructures and Microwave Dielectric Characteristics in Ba((Co0.6−x/2Zn0.4−x/2Mgx)1/3Nb2/3)O3 Ceramics

Abstract: Effects of postdensification annealing upon microstructures and microwave dielectric characteristics in Ba((Co 0.6Àx/2 Zn 0.4Àx/2 Mg x ) 1/3 Nb 2/3 )O 3 (x = 0, 0.1, 0.2, and 0.3) complex perovskite ceramics have been investigated. Long-time annealing at temperatures below the order-disorder transition temperature enhances the cation ordering degree and promotes the ordering domain growth. The most significant improvement of Qf value is obtained together with the suppressed temperature coefficient of resonant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 33 publications
0
68
0
Order By: Relevance
“…Therefore, The solid solutions of Ba(Co 0.7 Zn 0.3 ) 1/3 Nb 2/3 O 3 (BCZN) have been studied to obtain a zero-τ f material with high Q-value [3,4]. It is well known that the low loss of Ba(B 0 1/3 B″ 2/3 )O 3 is correlated with the 1:2 ordering in B-site cations and long-time low-temperature annealing are the most efficient way to enhance the cation ordering degree, consistent with the increase of Q Â f value [5,6]. Ahn et al [4] reported that the evaporation of CoO/ZnO existed in BCZN with the decreasing relative density.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, The solid solutions of Ba(Co 0.7 Zn 0.3 ) 1/3 Nb 2/3 O 3 (BCZN) have been studied to obtain a zero-τ f material with high Q-value [3,4]. It is well known that the low loss of Ba(B 0 1/3 B″ 2/3 )O 3 is correlated with the 1:2 ordering in B-site cations and long-time low-temperature annealing are the most efficient way to enhance the cation ordering degree, consistent with the increase of Q Â f value [5,6]. Ahn et al [4] reported that the evaporation of CoO/ZnO existed in BCZN with the decreasing relative density.…”
Section: Introductionmentioning
confidence: 98%
“…They are frequently used for the production of passive microwave components like substrates for integrated circuits, mounting, dielectric filters, dielectric antennae and dielectric resonators [1][2][3][4]. Among the dra- is highlighted for its high quality factor (Q 9 f) value, adjustable temperature coefficient of resonant frequency (s f ) and low sintering temperature among this series [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The samples with high ordering degree usually have low dielectric loss values (high Q 9 f values) [11,12]. Besides the 1:2 B-site cation ordering, there existed many literatures suggesting that the high Q 9 f characteristics were attributed to some other factors, such as impurity phases [13,14], porosity [15], lattice distortion (c/a) [16,17], grain size [18] and grain boundary [19], ordering domain structures [1,20,21], and oxygen vacancies [22]. Furthermore, the Q 9 f value of this system was considered to be very sensitive to nonstoichiometry [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…The result reveals that the intensity of (100) peak exhibiting an increase in the initial region (x = 0-0.02), but when the doping content exceeding x = 0.02, it decreases with increasing dopant amount. It has been reported that the evolution of ordering degree can be evaluated using a parameter (S) calculated by comparing the (100) (2h = 17.6°) superlattice reflection intensities with that of the strongest peak (110,102) from the below XRD patterns [30,31]: The ratio of the integral intensity of superlattice peak to the strongest peak in theory is calculated through placing all the atoms in ideal positions of the ordered hexagonal lattice. The S value with different x are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%